Pengaruh Penilaian Kinerja dengan ROI dan EVA terhadap Return Saham pada Perusahaan yang Tergabung dalam Indeks LQ 45 di Bursa Efek Indonesia - Ahfas, Mahfuz (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
There have been many investors who invest funds in certain companies. Thepurpose of the investment is to obtain the expected stock return. Investors, ininvesting certainly needs to look at whether the company will be turned intoinvestment activity to perform well or not, because only companies that have goodperformance that can provide the expected stock return. This research aims todetermine the effect of performance appraisal with the ROI and EVA on stockreturns. Sampling using purposive sampling techniques, the sample used is acompany incorporated in the LQ 45 index with period of August 2008 - January2009 and not included in the banking sector. This research uses secondary data,secondary data is financial statements in 2022-2023 of companies that were visitedin this research. Analytical model used to test the hypothesis is ModeratedRegression Analysis. Analysis conducted with the help of SPSS program. Theresults showed in partial ROI and EVA no effect on stock returns. Simultaneously,ROI and EVA variables also have no effect on stock returns. This is because stockprices are influenced by other factors beyond the company's performancemeasurement, among other factors of global economic conditions.